PNAES: limites e possibilidades da proteção social no contexto neoliberal - Costa, Natália Cristina Dreossi (2021)
The objective of this work is to analyze the nature and the meanings of the National Program of Student Assistance (PNAES) which can be found in the Presidential Decree 7.234/2010 in face of a neoliberal context. In order to accomplish that, a bibliographical and documentary research was performed. Furthermore, an analysis of the legal norms that regulate the Program was undertaken, i.e., the National Plan for Student Assistance (Fonaprace/Andifes, 2007), the Ordinance 39 from the Ministry of Education (BRASIL, 2007) and the Presidential Decree 7.234 (BRASIL, 2010). The analysis was performed utilizing the dialectical categories of human needs and wants, merit and rights of citizenship, inequality (related to formal/artificial equality) and substantive equality from Pereira (2016). It has been noticed that PNAES is close to characteristics that touch all the analytical categories utilized and that the justification of this fact resides on the Program corresponding to a social protection initiative within a capitalist context marked by neoliberalism. The conclusion reached is that PNAES can be identified with elements that define both social protection and social politics on neoliberalism.